A poesia e o sagrado: Hölderlin e Murilo Mendes e a lírica da modernidade - Menezes, Tenório Nunes Telles de (2025)
Poetic creation is a process of embodiment of feelings, worldviews, lived experiences and memories, incarnating as a language experience. This potency consolidates the poetic phenomenon and manifests the possibility of words evoking human existence and the relationship with reality and transcendence. The meaning of sacred is a recurring theme in literature and the basis of one expressive perspective in lyrical discourse: poetry with spiritual component. The study’s scope is founded on the purpose to question this subject in modernity, by discussing two poets who continued this tendency which finds in the divine its reference: – Friedrich Hölderlin: Complete Works of Poetry (as translated into Portuguese by João Barrento, here in free translation to English); and – Murilo Mendes: Metamorphoses and Convergence (both in free translation to English). The research aims to enunciate the relevance of lyrical tradition to the process of structuring poetic discourse itself, as well as its repercussions in modern times, underlining the pertinence in terms of reflection and comprehension of the world. This analytical trajectory will be conducted by the works of Martin Heidegger, Hans-Georg Gadamer, Paul Ricoeur, Walter Benjamin, Maurice Blanchot, María Zambrano, Octavio Paz, Giorgio Agamben and Benedito Nunes, while also referencing studies by F. M. Cornford, Mircea Eliade, Pierre Hadot, Julien Ries and Vilém Flusser on the significance and presence of the sacred in human’s social and cultural constitution process. The inquiry derives from discussing and identifying aesthetical elements and principles which materialize this poetic form, in addition to highlighting its importance in the history of Western poetry. The investigation focuses on modernity, with emphasis on the period regarding classicism and romanticism in German literature, and Brazilian modernism, observing formal and material evolution. The paper addresses the perspective of lyrical discourse which consists in the dialogue with the divine and its counterpart, the profane. Likewise, the proposition is to specify the aesthetical and historical foundations, along with effects in meaning, noting the implications for the formation process of our time, as an approach to understanding the world, posing meaning to existence, and a path to a reunion with human’s essence and transcendence in contemporaneity